2015
DOI: 10.1136/medhum-2014-010606
|View full text |Cite
|
Sign up to set email alerts
|

Narratives of neoliberalism: ‘clinical labour’ in context

Abstract: Cross-border reproductive care has been thrust under the international spotlight by a series of recent scandals. These have prompted calls to develop more robust means of assessing the exploitative potential of such practices and the need for overarching and normative forms of national and international regulation. Allied theorisations of the emergence of forms of clinical labour have cast the outsourcing of reproductive services such as gamete donation and gestational surrogacy as artefacts of a wider neolibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
26
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 14 publications
0
26
0
Order By: Relevance
“…Critical research has sufficiently demonstrated that neoliberal transformations result in numerous health implications, ranging from public policy to the commodification of the human body (Parry 2015), but experiences of the Hillside residents place political ecologies of health within a particular landscape in a particular political economic moment. At the same time, the ethnographic experiences articulated here speak to larger phenomena operating at global scales.…”
Section: Journal Of Political Ecologymentioning
confidence: 99%
“…Critical research has sufficiently demonstrated that neoliberal transformations result in numerous health implications, ranging from public policy to the commodification of the human body (Parry 2015), but experiences of the Hillside residents place political ecologies of health within a particular landscape in a particular political economic moment. At the same time, the ethnographic experiences articulated here speak to larger phenomena operating at global scales.…”
Section: Journal Of Political Ecologymentioning
confidence: 99%
“…Comparing the reproductive labor of oocyte donors and surrogates shows that the reproductive material of egg donors is differently valued and rewarded than the gestational services of surrogate mothers (Parry 2015c). Egg donors are rewarded on the basis of their physical appearance; the value given to their body is linked to post-colonial imaginaries of white beauty.…”
mentioning
confidence: 99%
“…Indian courts are still grappling with the issues involved in surrogacy. 9 The essential elements of surrogacy are childbearing by a surrogate mother, the termination of her parental rights after his birth, and payment of money by the genetic parents. If the money paid is merely to recompense the surrogate for the pain undertaken and includes reimbursement of medical and other expenses, then it is non-commercial surrogacy.…”
Section: Surrogacy: Legislative and Financial Aspectsmentioning
confidence: 99%